Assessment of quality control measures in the monitoring of microplastic: a critical review. Issue 1 (31st December 2023) - Gao, Wei; Deng, Xue-Jiao; Zhang, Jun; Qi, Lin; Zhao, Xiu-Qing; Zhang, Peng-Yu
ABSTRACT: Microplastics usually refer to solid plastic particles with particle size less than 5 mm. As a new type of pollutant unavoidable produced during human production and living activities, microplastics affect the ecological environment and human health safety. Since microplastics are widely distributed, small-sized microplastics and microfibers may be introduced from ambient air, sampling equipment and laboratory equipment during various monitoring process. Strict quality control measures were required to ensure the accuracy of monitoring results. In order to evaluate the compliance of quality control measures adopted in current researches, eight quality control parameters were statistically summarized by reviewing 30 published researches involving microplastic quality control methods. The results showed that those eight quality control measures could not be fully covered in most studies and uniform standardization of some key quality control measures have not been achieved. It was suggested to develop standardized operational protocols and perform cross-calibration among laboratories. GRAPHICAL ABSTRACT: uf0001